2018
DOI: 10.1038/s41467-018-05959-y
|View full text |Cite
|
Sign up to set email alerts
|

Single reach plans in dorsal premotor cortex during a two-target task

Abstract: In many situations, we are faced with multiple potential actions, but must wait for more information before knowing which to perform. Movement scientists have long asked whether in these delayed-response situations the brain plans both potential movements simultaneously, or if it simply chooses one and then switches later if necessary. To answer this question, we used simultaneously recorded activity from populations of neurons in macaque dorsal premotor cortex to track moment-by-moment deliberation between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 62 publications
7
76
2
Order By: Relevance
“…Subspaces enable inputs to co-exist with ongoing population activity. Although inputs, whether sensory 5,29 or cognitive such as during changes of mind 30,31 , influence motor cortical activity, the mechanisms that allow these inputs to coexist with ongoing population activity driving behavior have remained unclear. Intriguingly, motor cortex is dominated by apparently feedforward dynamics during the execution of planned or repetitive movements 14,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Subspaces enable inputs to co-exist with ongoing population activity. Although inputs, whether sensory 5,29 or cognitive such as during changes of mind 30,31 , influence motor cortical activity, the mechanisms that allow these inputs to coexist with ongoing population activity driving behavior have remained unclear. Intriguingly, motor cortex is dominated by apparently feedforward dynamics during the execution of planned or repetitive movements 14,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the influential affordance competition hypothesis (Cisek, 2012(Cisek, , 2007Cisek and Kalaska, 2010;Thura and Cisek, 2014), the brain specifies motor goals for competing options, in parallel, before deciding which one to execute (see also Klaes et al, 2011;Suriya-Arunroj and Gail, 2019). Although a number of behavioural and neurophysiological studies have expressed support for this hypothesis, alternative interpretations of the results of this work have been put forward; arguing that only a single motor goal is specified prior to target selection (Dekleva et al, 2018) or that the motor goal is specified only after target selection (Gallivan et al, 2018). Support for the affordance competition hypothesis comes from single cell recording studies that have employed delayed reach tasks in which one of two potential targets is cued after a preview period.…”
Section: Introductionmentioning
confidence: 92%
“…Importantly, most individual participants exhibited a mixture of encoding strategies across trials. This variability both within and across participants challenges that notion that any single model-i.e., parallel specification (e.g., Cisek, 2012), stay-or-switch (Dekleva et al, 2018) or serial-can account for participant behaviour.…”
Section: Target and Aimpoint Fixation Probabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these averaged reach movements can 79 be abolished by changes to either task instructions or constraints (Hudson et al, 2007;Chapman 80 and Goodale, 2010), suggesting that the averaged movement may reflect an optimal task strategy 81 rather than a competition between two motor plans (Wong and Haith, 2017). More 82 fundamentally, the neurophysiological evidence for multiple potential reach plans has recently 83 been questioned (Dekleva et al, 2018) in that the observed averaging may be an artifact caused 84 by combining neural activity across multiple trials rather than examining activity on an 85 individual trial-by-trial basis. Thus, it is still debated whether similar rules apply for saccades 86 and reaches when the brain has to resolve multiple potential motor plans.…”
mentioning
confidence: 99%